Groomincito: herramienta multimedia para la prevención y/o disminución de situaciones o casos de Grooming a través de la comunicación entre padres e hijos en la localidad de Kennedy, Bogotá (2021)
The internet has brought multiple benefits to society breaking down the barriers of knowledge and allowing us to get close to people who are thousands of kilometers away, however, it has opened the possibility for ill-intentioned people to cause harm especially to underage, therefore, today it talk about problems like cyberbullying, sexting, cyberbullying, grooming, among others. getting closer These types of problems can become so serious that they transcend the screen and manage to cause psychological and physical damage such as sexual abuse of underage. This is the main cause that motivated us to contribute to the prevention of the grooming problem, understood as the action of an adult to impersonate an underage with the objective of obtaining naked images of the underage or performing a sexual act and in some cases achieving a rape. Within this framework of ideas, the project generates an alternative to prevent grooming in girls between the ages of twelve and fourteen, taking as a premise the importance of communication between parents and daughters as a preventive factor. For this, two methodologies are used, that of Bruno Munari and that of Asimov in order to reach an optimal result. Following this order, the panorama is analyzed from a global level and it is possible to focus the problem in a local context (Kennedy locality in Bogotá). The investigation of this topic begins by subdividing the case study into five areas, educational, social, health, legal, personal, delving into the causes and consequences related to grooming, it is in this part where it is analyzed in which link we can participate, it is had in some products developed from the digital design and its pros and cons are evaluated to build a prototype according to the needs of the users. Answering the question, how can trust between such different users be strengthened and mutual interest generated? The idea arises of doing it through a recreational space around a board game that carries behind a whole universe of knowledge.